Indeks Topologi Padmakar Ivan dan Szeged pada Graf Koprima Prima dari Grup Bilangan Bulat Modulo - Abdurahim, Abdurahim; Pratiwi, Lia Fitta; Karang, Gusti Yogananda; Wardhana, I Gede Adhiya Wisnu; Irwansyah, Irwansyah; Awanis, Zatta Yumni; Romdhini, Mamika Ujianita (UIN Walisongo Semarang, 2024)
The Prime Coprime Graph is defined as a graph in which two distinct vertices are adjacent if and only if the greatest common divisor of their orders is 1, indicating that they are coprime. This research focuses on deriving general formulas for the Padmakar-Ivan index and the Szeged index for the coprime prime graph of the modulo integer group with n=p^k, where p is a prime number and k is not less than 2. As a result of this study, explicit formulas for the Padmakar-Ivan and Szeged indices were obtained, along with an analysis of the relationship between these two indices.Keywords: prime coprime graph, Padmakar-Ivan index, Szeged index.